Flavonoid profile of Anoectochilus roxburghii (Wall.) Lindl. Under short-term heat stress revealed by integrated metabolome, transcriptome, and biochemical analyses - Cui, Meng (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.